PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA MELALUI MOTIVASI KERJA PEGAWAI DI KANTOR CAMAT TASIK PUTRI PUYU - Selamet Riadi; Indra Prasetyo; Woro Utari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The purpose of the study was to describe organizational culture, commitment, motivation and employee performance at the Tasik Putri Puyu Sub-district Office. To know and analyze the influence of organizational culture, commitment to motivation. The influence of motivation, organizational culture, commitment to employee performance, the influence of organizational culture and commitment to employee performance through motivation. Population and sample amounted to 31 people. The sampling technique used the census sampling method. Data were collected through questionnaires and documentation. Data analysis methods include validity testing, reliability testing and path analysis. The results of the analysis show that organizational culture, employee commitment, employee work motivation and employee performance at the Tasik Putri Puyuh sub-district office are all in high condition. Organizational culture does not have a significant influence on employee work motivation. Commitment has a significant effect on employee motivation. Work motivation has a significant influence on employee performance. Organizational culture has no significant effect on employee performance. Commitment has a significant effect on employee performance. Organizational culture has no significant effect on performance through work motivation. Commitment has a significant effect on performance through work motivation.